Sibling Rivalry And Aggressiveness On The Student Of MTSN 4 Banda Aceh - Ria Muranda; Nurdin Bakrie; Rawdhah Binti Yasa (Program Studi Bimbingan Konseling dan Pendidikan Islam, 2022)
One of the conflicts that often arises in fraternal relationships is sibling rivalry. Sibling rivalry is a competition or an effort to outperform each other among siblings that also occurs during adolescence, to fight over things like attention, and love of parents. Sibling rivalry in adolescents can lead to aggressiveness. One serious aspect in sibling rivalry is that the pattern of bad relationships such as showing aggressive behavior which becomes a pattern of social relations that teenagers will take out of the house to be applied in relationships with peers. This study aimed to determine how the relationship between sibling rivalry and aggressiveness on the students of MTsN 4 Banda Aceh. This research used quantitative methods with the technique of determining non-random sampling samples, namely purposive sampling. The population in this study were all students of MTsN 4 Banda Aceh totaling 314 students with 117 students as the samples. The results showed that there was a positive relationship between sibling rivalry with aggressiveness on the students of MTsN 4 Banda Aceh. With analysis based on the Pearson correlation test shows that the value of r = 0.423 is a positive correlation, p = 0,000 (p <0.05). From the results of the analysis, it can be stated that there is a significant positive relationship between sibling rivalry with aggressiveness on the students of MTsN 4 Banda Aceh. Abstrak Salah satu konflik yang sering timbul pada hubungan persaudaraan adalah sibling rivalry. Sibling rivalry merupakan persaingan atau usaha saling mengungguli antar saudara kandung yang juga terjadi pada masa remaja, untuk memperebutkan sesuatu seperti perhatian, dan cinta orang tua. Sibling rivalry pada remaja dapat memicu timbulnya agresivitas. Salah satu aspek yang serius dalam sibling rivalry, bahwa pola hubungan buruk seperti menunjukkan perilaku agresif ini sering menjadi pola hubungan sosial yang akan dibawa remaja keluar rumah untuk diterapkan dalam hubungannya dengan teman sebaya. Penelitian ini bertujuan untuk mengetahui bagaimana hubungan sibling rivalry dengan agresivitas pada siswa MTsN 4 Kota Banda Aceh. Penelitian ini menggunakan metode kuantitatif dengan teknik penentuan sampel non random sampling yaitu purposive sampling. Populasi dalam penelitian ini adalah seluruh siswa MTsN 4 Kota Banda Aceh berjumlah 314 siswa dengan diperoleh sampel 117 siswa. Hasil penelitian menunjukkan bahwa terdapat hubungan yang positif antara sibling rivalry dengan agresivitas pada siswa MTsN 4 Kota Banda Aceh. Dengan analisis berdasarkan uji korelasi Pearson dan menunjukkan bahwa nilai r= 0,423 merupakan korelasi positif, p=0,000 (p<0,05). Dari hasil analisis tersebut dapat dikatakan bahwa terdapat hubungan positif yang signifikan antara sibling rivalry dengan agresivitas pada siswa MTsN 4 Kota Banda Aceh.